The Effect of Npk Fertilizer on The Growth and Oil Production of Sunflower (Helianthus Annuus L.) - Irawan, Eriza; Kanny, Putri Irene; Kalsum, Ummu; Saputry, Dinda Helma (International Journal on Food, Agriculture and Natural Resources, 2025)
This electronic document is a “live” template and already defines the components of your paper [title, text, heads, etc.] in its style sheet.  *CRITICAL:  Do Not Use Symbols, Special Characters, Footnotes, or Math in Paper Title or Abstract. (Abstract) This study aims to analyze the response of different doses of NPK compound fertilizer on the growth and oil production of sunflower (Helianthus annuus L.). It is necessary to increase the production of sunflower oil by applying the appropriate dose of NPK fertilizer to meet the demands of the oil market. This study used a Randomized Complete Block Design (RCBD), with 4 experimental treatments: NPK compound fertilizer doses of 2.5 g/plant, 3.75 g/plant, 5 g/plant and 6.25 g/plant. The results showed significant positive effects of NPK fertilization on vegetative growth parameters, specifically plant height and stem diameter. However, the fertilizer treatments did not show significant impact on sunflower oil production. Based on the observed results, the 3.75 g/plant dose (D2) was the most effective NPK dose for the parameters of leaf number, flower diameter, flower weight, seed wet weight, seed dry weight.